2020
DOI: 10.18502/ijm.v12i2.2622
|View full text |Cite
|
Sign up to set email alerts
|

Survey of WU and KI polyomaviruses, coronaviruses, respiratory syncytial virus and parechovirus in children under 5 years of age in Tehran, Iran

Abstract: Background and Objectives: Severe acute respiratory infections (SARI) remain an important cause for childhood morbid- ity worldwide. We designed a research with the objective of finding the frequency of respiratory viruses, particularly WU and KI polyomaviruses (WUPyV & KIPyV), human coronaviruses (HCoVs), human respiratory syncytial virus (HRSV) and human parechovirus (HPeV) in hospitalized children who were influenza negative. Materials and Methods: Throat swabs were collected from children younger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 32 publications
(29 reference statements)
4
5
0
Order By: Relevance
“…HCoV‐HKU1 was reported to be the cause of 0.04% to 2.1% of adult respiratory diseases around the world, 25 and also in Iran based on our analysis, which was detected in 2% of studied subjects with a respiratory infection. HCoV‐HKU1 was found as both a single and mixed with other respiratory viruses in studies from Iran 26 . In our investigation, similar to other studies, respiratory symptoms were the most common clinical manifestations of HCoV‐HKU1; however, nonrespiratory involvements are also described such as gastrointestinal symptoms (e.g., diarrhea) 25 .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…HCoV‐HKU1 was reported to be the cause of 0.04% to 2.1% of adult respiratory diseases around the world, 25 and also in Iran based on our analysis, which was detected in 2% of studied subjects with a respiratory infection. HCoV‐HKU1 was found as both a single and mixed with other respiratory viruses in studies from Iran 26 . In our investigation, similar to other studies, respiratory symptoms were the most common clinical manifestations of HCoV‐HKU1; however, nonrespiratory involvements are also described such as gastrointestinal symptoms (e.g., diarrhea) 25 .…”
Section: Discussionsupporting
confidence: 88%
“…HCoV-HKU1 was found as both a single and mixed with other respiratory viruses in studies from Iran. 26 In our investigation, similar to other studies, respiratory symptoms were the most common clinical manifestations of HCoV-HKU1; however, nonrespiratory involvements are also described such as gastrointestinal symptoms (e.g., diarrhea). 25 Most of the HCoV-HKU1-infected cases in our study (10 out of 12 virus-infected cases) were hospitalized for the severity of their illness.…”
Section: Demographics Prevalence and Seasonalitysupporting
confidence: 91%
“…Accordingly, a positive sample is a sample that both orf1ab and N genes are positive. In addition, it should be noted that newly reported Taq-man Multiplex Real-Time PCR has been utilized for finding of human coronaviruses such as SARS-CoV-2 RNA and human respiratory syncytial virus (HRSV) in samples of wastewater and hospitalized children [59][60][61].…”
Section: Resultsmentioning
confidence: 99%
“…The current study detected 1(0.88%) out of 113 (100%) of WUPyV DNA in plasma of chronic kidney disease patients while dosent detect any isolate of WUPyV in plasma of urinary tract infections patients. The result of both groups is compatible to with Csoma et al, (2011) (10) which detect 0.8 of WUPyV in blood from renal transplant patients as well as to csoma et al, (2012) (20) which dosent detect WUPyV DNA in plasma of pregnant and non-pregnant women as well as to Limam et al, (2020) (22) which not detected WUPyV out of 112 from Tunisian patients but is incompatible to Csoma et al, (2014) which record from 9.1% and 5.3% of WUPyV in plasma samples in addition to Aghamirmohammadli et al, (2020) (4) which revealed 1.5% of WUPyV in children under (7.84 %) and (3.22 %) for female and male patients respectively . There was no significant difference (Chi-square = 1.19 ; P value = 0.27) among male and female according to KIPyV detection and distribution.…”
Section: Prevalence Of Kipyv and Wupyv In Study Groupsmentioning
confidence: 94%
“…The site of persistent infection of these two viruses across the lifespan still unclear (4) . These two viruses are closely related to each other than to SV40, BK and JC, but, as shown by the amino acid identity and phylogenetic analysis ratio, they vary greatly from each other (5) .…”
Section: Introductionmentioning
confidence: 99%